Supplemental Dietary Selenohomolanthionine Improve Antioxidant Activity and Immune Function in Weaned Beagle Puppies - Shao, Chunyan; Zheng, Moufeng; Yu, Ziwei; Jiang, Sheng; Zhou, Bin; Song, Quanjiang; Ma, Tianning; Zhou, Yingshan; Dong, Wanyu; Li, Ding; Gu, Yao; Wang, Xiaodu; et al. (Frontiers in Veterinary Science, 2021)
The purpose of this study was to investigate the effects of dietary Selenohomolanthionine (SeHLan) on antioxidant status and immune response in canine parvovirus (CPV) vaccinated puppies. In this study, thirty weaned puppies were randomly divided into six groups: control group (-Se/-Vacc), immunization group (-Se/+Vacc), supplementation of sodium selenite group (SS/+Vacc, 0.35 mg/kg DM), low-dose SeHLan group (SeHLan-L/+Vacc, 0.35 mg/kg DM), mid-dose SeHLan group (SeHLan-M/+Vacc, 1.0 mg/kg DM), and high-dose SeHLan group (SeHLan-H/+Vacc, 2.0 mg/kg DM). The puppies were fed for 42 days and vaccinated with Vanguard Plus 5 on day 0 and day 21. Blood samples were collected on 7, 14, 21, 28, 35, 42 days post-immunization (PI) for determination of antioxidant indicators, lymphocyte proliferation index, serum cytokine concentration (IL-2, IL-4), canine polymorphonuclear neutrophils (PMN) phagocytic function, and the level of CPV antibody titers. The results showed that SeHLan supplementation raised the serum Se concentration and glutathione peroxidase (GSH-Px) activity in a dose-dependent manner (P<0.05). It also increased the activity of serum superoxide dismutase (SOD) and decreased serum malondialdehyde (MDA) content, especially in SeHLan-M/+Vacc group (1.0 mg/kg DM) (P<0.01). SeHLan supplementation significantly increased lymphocyte proliferation, IL-2, and IL-4 levels in canine serum, and enhanced phagocytosis of PMN in vaccinated puppies (P<0.05). Moreover, SeHLan supplementation shortened the CPV antibody production time and increased the CPV antibody titers (P<0.05). Of note, the beneficial effects of SeHLan were superior to those of SS. In conclusion, dietary SeHLan supplementation improved antioxidant activity, increased CPV antibody titers, and enhanced immune function in puppies after weaning. An appropriate dosage of SeHLan (1~2mg/kg DM) may confer nutritional benefits in puppies.